Understanding the Mechanisms Behind the Response to Environmental Perturbation in Microbial Mats: A Metagenomic-Network Based Approach - De Anda, Valerie; Zapata-Peñasco, Icoquih; Blaz, Jazmín; Poot-Hernández, Augusto Cesar; Contreras-Moreira, Bruno; González-Laffitte, Marcos; Gámez-Tamariz, Niza; Hernández-Rosales, Maribel; Eguiarte, Luis E.; Souza, Valeria (Frontiers in Microbiology, 2018)
Human activities impact ecosystems at all levels of complexity of life including microbial communities, which are responsible for driving the main cycles on Earth. So far, it is unclear whether these perturbations influence the dynamics of microbial communities and what are the general patterns that arise in response to a disturbance and whether it is possible to predict them. We suggest the use of microbial mats as a model of study to reveal patterns that can both, illuminate the ecological processes underlying microbial dynamics, and contribute to a better understanding of the relationship between stability and response to stress. We traced the response of environmental perturbation caused by water depletion in microbial mats in the endangered oasis of Cuatro Cienegas Basin, Mexico. By using a time-series metagenomics study of 2 years in 3 nearby sampling sites, we implemented three approaches in addition to standard ecological analysis. First, the use of the Multi-genomic Entropy Based Score (MEBS) to evaluate the dynamics of the entire biogeochemical cycles across temporal-spatial scales; second the use of robust Time Series-Ecological Networks (TS-ENs) to evaluate the whole repertoire of interactions at every taxonomic level; and finally the use of network motifs to characterize site-specific interactions. Our results highlight the enormous taxonomic diversity within the microbial mats with at least 100 phyla, mainly represented by members of the rare biosphere (97.27%). Microbial mats were resistant over time measured by ecological indexes. However, statistical analyses suggest a clear involvement of anaerobic guilds related to the sulfur and methane cycles during water conditions in contrast to dry conditions, where there is an increase in fungi, photosynthetic, and halotolerant taxa. Despite being broadly taxonomically unique, microbial mats share a core of 373 genera present in all samples. The results of the TS-ENs indicate that in water conditions, there was an equilibrium between negative-positive interactions, while under desiccation there is an increase of negative relationships. We suggest that mechanisms behind the observed resilience could include: a great taxonomic diversity represented by a community in which all members are interacting with each other (low modularity), a large number of taxa from the